S54 The lung microbiome in nontuberculous mycobacterial pulmonary disease. (11th November 2022) - Kumar, K; Cuthbertson, L; Ellis, HC; Churchward, C; Loebinger, MR; Moffatt, MF; Cookson, WOC
Abstract : Introduction and Objectives: Nontuberculous mycobacterial pulmonary disease (NTM-PD) incidence is rising. 16S rRNA gene sequencing has demonstrated that the lung microbiome has a role in the pathogenesis of pulmonary diseases. Data on the relationship between the lung microbiome and NTM-PD are limited. We aimed to quantify the total pulmonary bacterial burden in NTM-PD patients and characterise changes in their lung microbiome over time. Methods: Sputum samples were acquired longitudinally at baseline, weekly for 4 weeks and then monthly up to 3 months from 37 patients who either had NTM-PD and were starting NTM treatment; had NTM-PD but did not require treatment; or did not have NTM-PD. Sputum DNA was extracted using a hexadecyl-trimethyl-ammonium bromide phenol chloroform protocol. Total bacterial burden was quantified using 16S rRNA gene SYBR green quantitative polymerase chain reaction. 16S rRNA gene sequencing was performed on an Illumina MiSeq™ Next Generation Sequencer. Statistical analysis was performed in R version 4.1.3. Results: At baseline, sputum biomass was higher in Mycobacterium avium complex (MAC) pulmonary disease (MAC-PD) patients than M. abscessus (MAB) pulmonary disease (MAB-PD) patients ( P<0.05 ); there was no significant difference at 3 months. Alpha diversity measures (richness, Shannon index, Simpson index, Pielou's evenness index) were higher among MAC-PD than MAB-PD patients at baseline and at 3 months ( P<0.05 for all measures). Beta diversity measured using the Bray-Curtis dissimilarity index significantly differed between the MAC-PD, MAB-PD and non-NTM groups at baseline ( P<0.05 ) and at 3 months ( P<0.01 ). Richness was lower in the MAC-PD treatment group compared to the non-treatment group at 3 months ( P<0.05 ); there were no other differences between these groups in diversity or sputum biomass at baseline or 3 months. There was a higher mean abundance of Pseudomonas in the MAB-PD non-treatment group compared to the MAB-PD treatment group and the MAC-PD non-treatment or treatment groups across all timepoints ( figure 1 ). Conclusion: Our study demonstrates that the lung microbiome is influenced by the presence of MAC and MAB. This may impact progression and prognosis in NTM-PD. Further investigation will evaluate how lung microbiome perturbations correlate with clinical parameters and identify biomarkers of NTM pathogenicity and treatment response. Please refer to page A210 for declarations of interest related to this abstract.